Advances in modelling the transport of heavy metals in agricultural soils and their leaching into groundwater: an integrative critical review - Ramos-Romero, Steven Stalin; Benavides-Rosales, Hernán Rigoberto; Peña-Chamorro, Julio Jairo (Frontiers in Environmental Science, 2026)
This systematic review examines recent advances in modelling the transport of heavy metals in agricultural soils and their potential leaching into groundwater. Following the PRISMA 2020 guidelines, peer-reviewed studies published between 2020 and 2025 were systematically identified and analysed to assess the physicochemical, hydrological, and geochemical processes governing the mobility of key contaminants, including cadmium (Cd), zinc (Zn), lead (Pb), copper (Cu), and nickel (Ni). The reviewed evidence indicates that metal transport is primarily controlled by soil properties such as pH, texture, organic matter content, and redox conditions, in combination with hydrodynamic drivers related to irrigation practices, extreme rainfall events, and climatic variability. Numerical and reactive transport models, particularly HYDRUS-1D and PHREEQC, were the most frequently applied tools for simulating vertical migration, breakthrough behaviour, and long-term contamination scenarios. The results further show that intensive agricultural management, the reuse of treated wastewater for irrigation, and proximity to mining or industrial sources significantly increase the mobile fraction of heavy metals, thereby enhancing the risk of contaminant transfer into shallow aquifers. Extreme hydrometeorological events were found to accelerate metal redistribution even in soils previously considered geochemically stable. Overall, this review highlights the need for integrated, multi-scale modelling approaches that combine experimental data, advanced geochemical analysis, and numerical simulations. Such approaches are essential to improve predictive accuracy and to support the development of sustainable soil and groundwater management strategies under increasing environmental and climatic pressures.